2021
DOI: 10.1016/j.jlr.2021.100092
|View full text |Cite
|
Sign up to set email alerts
|

Shark liver oil supplementation enriches endogenous plasmalogens and reduces markers of dyslipidemia and inflammation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…The most interesting finding from this study was that ether phospholipids in plasma showed significantly greater incorporation of EPA and DHA following KO than FO treatment. We propose that ether phospholipids present in the KO contributed to increased ether phospholipid concentrations in plasma, since circulating plasmalogens are either derived from dietary sources and/or are synthesized in the liver and gastrointestinal epithelium (Roels et al, 1987, Astarita et al, 2010, Paul et al, 2021. In the present study, alkyl-phosphatidylcholine (PakCho) and lyso-PakCho were the main species detected in the KO supplement, accounting for 7% of the choline phospholipids, with PC(O-36:5), PC(O-16:0-22:6), LPC(O-16:1), LPC(O-18:1), and PC(O-32:1) accounting for 6% (Sung et al, 2019).…”
Section: General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The most interesting finding from this study was that ether phospholipids in plasma showed significantly greater incorporation of EPA and DHA following KO than FO treatment. We propose that ether phospholipids present in the KO contributed to increased ether phospholipid concentrations in plasma, since circulating plasmalogens are either derived from dietary sources and/or are synthesized in the liver and gastrointestinal epithelium (Roels et al, 1987, Astarita et al, 2010, Paul et al, 2021. In the present study, alkyl-phosphatidylcholine (PakCho) and lyso-PakCho were the main species detected in the KO supplement, accounting for 7% of the choline phospholipids, with PC(O-36:5), PC(O-16:0-22:6), LPC(O-16:1), LPC(O-18:1), and PC(O-32:1) accounting for 6% (Sung et al, 2019).…”
Section: General Remarksmentioning
confidence: 99%
“…Another rat study reported that when 0.1% of the diet (weight %) was fed as plasmalogens from chicken skin (PlsEtn), the relative compositions of erythrocyte PlsEtn and PtdEtn increased after 4 weeks (Mawatari et al, 2012). Paul et al (2021) recently showed that plasma accumulated highly polyunsaturated species of alkyl and alkenyl PtdCho and PtdEtn following the consumption of alkylglycerols containing fatty acids with fewer double bonds, indicating that rearrangement of the fatty acyl component of alkyl lipids occurs following digestion and absorption. Furthermore, it was clear that alkyl species had been metabolized to plasmalogens (PlsEtn and PlsCho).…”
Section: What Is the Evidence That Dietary Plasmalogens Are Bioavaila...mentioning
confidence: 99%
“…460 kg of scallops. In the bottom the alkyl chain distribution of shark liver oilpurified AG (from [92]). (B) PE-Pls is the major plasmalogen found in chicken skin and scallops.…”
Section: Small Molecules Used In Prtmentioning
confidence: 99%
“…Plasmalogens are transported from the intestine and liver to other organs, but it On top is a generic chemical structure of an AG. In the bottom the alkyl chain distribution of shark liver oil-purified AG (from [92]). (B) PE-Pls is the major plasmalogen found in chicken skin and scallops.…”
Section: Small Molecules Used In Prtmentioning
confidence: 99%
“…AKGs are considered to be important immune-stimulating factors, able to increase the number of leucocytes, lymphocytes and platelets [10]. In vitro and in vivo studies suggest that AKG may offer anti-tumor potential via activating macrophage and exerting anti-angiogenesis effects [13][14][15]. Aside from activating macrophages, AKGs stimulate antibody production and enhance the function of Fc-receptors in the immune system [12,16].…”
Section: Introductionmentioning
confidence: 99%